Long-Term and Lasting Impacts of Personal Initiative Training on Entrepreneurial Success - Francisco Campos; Michael Frese; Leonardo Iacovone; Hillary C. Johnson; David McKenzie; Mona Mensmann (Institute of Labor Economics (IZA), 2025)
A randomized experiment in Togo found that personal initiative training for small businesses resulted in large and significant impacts for both men and women after two years. We revisit these entrepreneurs after seven years, and find long-lasting average impacts of personal initiative training of 91 higher profits per month, which is larger than the 2-year impacts. However, these long-term impacts are very different for men and women: the impact for men grows over time as they accumulate more capital and increase self-efficacy, whereas the impact for women is flat or declines, and capital build-up is much more limited.
Keywords: O12; O17; L26; J24; J16; D22; 330; microentrepreneurship; business training; personal initiative; firm growth